1999
DOI: 10.1016/s0928-8244(99)00024-3
|View full text |Cite
|
Sign up to set email alerts
|

Metronidazole resistance and virulence factors in Helicobacter pylori as markers for treatment failure in a paediatric population

Abstract: The eradication rate obtained using the classical triple therapy containing metronidazole, amoxicillin and bismuth citrate, was determined in 57 paediatric patients with digestive disorders, according to the susceptibility to metronidazole of the Helicobacter pylori strains (determined by agar dilution) and the cagA and vacA status (determined by PCR). Eradication was obtained in 38 out of 43 patients (88.3%) infected by H. pylori with metronidazole MIC < or = 2 mg l(-1), in 3 out of 6 patients (50%) when MIC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…There is very limited information on the impact of clarithromycin and metronidazole resistance on H. pylori eradication in children. We have identified few clinical trials over the last two decades which evaluate the clinical outcome of H. pylori triple therapies with respect to pre-treatment susceptibility testing to clarithromycin and metronidazole (16,19,(43)(44)(45)(46). Despite the very limited number and power of pediatric clinical trials including susceptibility testing, the effect of resistance on treatment outcome was more pronounced for clarithromycin than for metronidazole (Table II).…”
Section: Factors Affecting Eradication Ratementioning
confidence: 99%
See 1 more Smart Citation
“…There is very limited information on the impact of clarithromycin and metronidazole resistance on H. pylori eradication in children. We have identified few clinical trials over the last two decades which evaluate the clinical outcome of H. pylori triple therapies with respect to pre-treatment susceptibility testing to clarithromycin and metronidazole (16,19,(43)(44)(45)(46). Despite the very limited number and power of pediatric clinical trials including susceptibility testing, the effect of resistance on treatment outcome was more pronounced for clarithromycin than for metronidazole (Table II).…”
Section: Factors Affecting Eradication Ratementioning
confidence: 99%
“…As gastric inflammation increases mucosal blood flow, it has been hypothesized this may help the diffusion of antibiotics. Nonetheless, despite the limited experience in children, Lopez-Brea et al showed in 57 pediatric patients that the cagA status was not an important factor in treatment failure in the eradication of H. pylori following the triple therapy containing metronidazole, amoxicillin and bismuth citrate (46). vacA gene status.…”
Section: Factors Affecting Eradication Ratementioning
confidence: 99%
“…This hypothesis suggests an involvement of histological damage in therapeutic outcome, although no clear details are available on this topic. However, in some reports, no correlation has been found between cagA/vacA status and the eradication rate 17 . Finally, no data are available on the therapeutic outcome in relation to iceA .…”
Section: Introductionmentioning
confidence: 97%
“…However, in some reports, no correlation has been found between cagA ⁄ vacA status and the eradication rate. 17 Finally, no data are available on the therapeutic outcome in relation to iceA. Differences in the predominant strain in different geographical regions may account for the different therapeutic results.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Van Doorn et al[8] pointed out that vacA s1 strains had higher H . pylori eradication rates compared with vacA s2 strains, but López-Brea et al[9] indicated there was no difference between vacA s1 and vacA s2 strains. Similarly, for vacA m1 and vacA m2, Niu et al[10] reported that eradication rates were higher with vacA m1 strains.…”
Section: Introductionmentioning
confidence: 99%